Responsibility to protect a defense - Bellamy, Alex J. 1975- (Oxford University Press, 2015)
The Responsibility to Protect (R2P) principle is the international community's major response to the problem of genocide and mass atrocities - a problem seen in Bosnia, Rwanda and more recently in Syria. This book argues that although it is far from perfect R2P offers the best chance we have of building an international community that works to prevent these crimes and protect vulnerable populations. To make this argument, the book sets out the logic of R2P and its key ambitions, examines some of the critiques of the principle and its implementation in situations such as Libya, and sets out ways of overcoming some of the practical problems associated with moving this principle from words into deeds